The Effect Of Job Satisfaction On The Organizational Commitment Of Nurses At RSUD Kota Makassar - Nurul Hidayah Nur (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2023)
Job satisfaction reflects one's feelings towards their work, when someone is satisfied with their work, they will be more committed to the organization. This study aims to analyze the effect of job satisfaction on organizational commitment at the RSUD Kota Makassar. The type of research conducted is a quantitative study using an observational study with a cross sectional study design. Sampling used stratified random sampling so that the sample in this study were nurses who served in the Inpatient Installation, IGD, ICU and OK RSUD Kota Makassar totaling 104 respondents. The results showed that there was an effect of job satisfaction on organizational commitment. This study indicates that the high level of nurse satisfaction at RSUD Kota Makassar is able to create a sense of pride and trust in nurses, increase the emotional attachment of nurses to their organization and create a strong desire to continue working in their organization and have a high responsibility to stay afloat in their organization. hospital. It is recommended to the hospital management to pay more attention to the job satisfaction of nurses by creating a safe and comfortable work environment, including a clean room, good air circulation, adequate lighting facilities, and adequate health support equipment according to the needs of implementing nursing actions.